2000
DOI: 10.1002/hep.510310320
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of reduced insulin sensitivity and secretion to the pathogenesis of hepatogenous diabetes: Effect of liver transplantation

Abstract: Diabetes mellitus frequently complicates cirrhosis but the pathogenic mechanisms are unknown. To assess the contribution of reduced insulin action and secretion, 24 cirrhotic-diabetic patients waiting for liver transplant because of an unresectable hepatocarcinoma underwent an oral glucose tolerance test (OGTT) to assess the ␤-cell function and an insulin clamp combined with [3-3 H]glucose infusion to measure whole body glucose metabolism before and 2 years after the transplant. Seven cirrhotic nondiabetic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 39 publications
10
96
0
3
Order By: Relevance
“…A recent report from Italy may help explain these findings. 8 In their study, Perseghin et al found that patients with cirrhosis with DM may have insulin resistance and reduced ␤-cell function. The first of these 2 alterations is reversed after OLT, but reduced ␤-cell secretion is not.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent report from Italy may help explain these findings. 8 In their study, Perseghin et al found that patients with cirrhosis with DM may have insulin resistance and reduced ␤-cell function. The first of these 2 alterations is reversed after OLT, but reduced ␤-cell secretion is not.…”
Section: Discussionmentioning
confidence: 96%
“…Glucose intolerance and insulin resistance of patients with cirrhosis are reversed after orthotopic liver transplantation (OLT), 8 but the use of such immunosuppressive drugs as cyclosporine, tacrolimus, or prednisone can alter glucose metabolism either by direct effect on pancreatic ␤-cells or by contributing to insulin resistance. [9][10][11] Thus, the global effect of OLT on glucose metabolism may be both prodiabetogenic and antidiabetogenic.…”
mentioning
confidence: 99%
“…10 In addition, there may be a component of defective insulin secretion by the pancreatic beta cell in some cirrhotics, notwithstanding the elevated circulating insulin levels commonly found in cirrhosis. 11 Chronic hyperinsulinemia itself may be the cause of insulin resistance, because the latter is ameliorated if blood insulin levels can be lowered for a prolonged period of time. 12 Theoretically, at least, liver transplantation could cure hepatogenous diabetes, because removal of the diseased liver should reverse the insulin resistance of cirrhosis and permit normal glucose handling and carbohydrate metabolism.…”
Section: Pathogenesis and Prevalence Of Diabetes In Liver Transplant mentioning
confidence: 99%
“…An improvement in glucose tolerance has been recognized in HCV-positive diabetic patients following liver transplantation, even without complete regression of insulin resistance [10]. In fact, transplanted patients still maintained the reduced muscle glucose uptake and the decreased non-oxidative glucose disposal observed before transplantation, indicating persistence of insulin resistance in peripheral tissues, particularly in the skeletal muscle [9,10]. Glucose metabolism has also been evaluated in patients with cirrhosis of viral aetiology, in which impaired insulin action has been detected.…”
Section: Viral Hepatitismentioning
confidence: 99%
“…Glucose metabolism impairment becomes worse with the progression of chronic hepatitis to liver cirrhosis. In cirrhotic patients, the prevalence of impaired glucose tolerance (IGT) is estimated to be about 60-80% [9,10], and that of overt diabetes is about 7-15%. Since, in CLD, numerous aetiological, environmental, nutritional and metabolic factors are involved, and the term CLD embraces different stages of liver dysfunction, the pathogenic mechanisms underlying the relationship between IGT or diabetes and CLD remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%